2017
DOI: 10.1002/jcp.26249
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, hemostasis, thrombosis, and coagulation

Abstract: Atherothrombotic cardiovascular disease is a major cause of mortality throughout the world. Platelet activation and aggregation play a central role in hemostasis and thrombosis. Herbal medicines have been traditionally used in the management of cardiovascular disease and can help in modifying its progression, particularly in hemostasis and the coagulation process, as well as altering platelet function tests and some coagulation parameters. Curcumin is a polyphenol derived from the Curcuma longa plant and has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 170 publications
(90 citation statements)
references
References 123 publications
(146 reference statements)
0
77
0
2
Order By: Relevance
“…However, approved drugs for the treatment of cancer are usually limited by potential undesirable side effects such as hepatotoxicity, nephrotoxicity, ototoxicity, reduction in platelet counts, and myelosuppression . Curcumin, a natural polyphenolic compound and the principal coloring agent found in the rhizomes of Curcuma longa (Zingiberaceae), has several health benefits, including antioxidant , anti‐inflammatory , immunomodulatory , antiarthritic , antithrombotic , pulmonoprotective , lipid‐modifying , neuroprotective , anticancer , antidiabetic, and hepatoprotective properties. Numerous reports have indicated that curcumin is quite safe and nontoxic to humans up to doses of 12 g/day .…”
Section: Introductionmentioning
confidence: 74%
“…However, approved drugs for the treatment of cancer are usually limited by potential undesirable side effects such as hepatotoxicity, nephrotoxicity, ototoxicity, reduction in platelet counts, and myelosuppression . Curcumin, a natural polyphenolic compound and the principal coloring agent found in the rhizomes of Curcuma longa (Zingiberaceae), has several health benefits, including antioxidant , anti‐inflammatory , immunomodulatory , antiarthritic , antithrombotic , pulmonoprotective , lipid‐modifying , neuroprotective , anticancer , antidiabetic, and hepatoprotective properties. Numerous reports have indicated that curcumin is quite safe and nontoxic to humans up to doses of 12 g/day .…”
Section: Introductionmentioning
confidence: 74%
“…Curcumin is relatively safe and nontoxic; its therapeutic approach exhibits a diverse range of biological effects, such as anti-inflammatory (Panahi, Hosseini, et al, 2015;Sahebkar, Cicero, Simental-Momtazi et al, 2016), anticoagulant (Keihanian, Saeidinia, Bagheri, Johnston, & Sahebkar, 2018), hepatoprotective (Rahmani et al, 2016), analgesic (Sahebkar & Henrotin, 2016), antidiabetic (Panahi, Khalili, et al, 2018), lipid-lowering (Panahi, Kianpour, et al, 2016), and antidepressant (Panahi, Badeli, Karami, & Sahebkar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1, 7-bis (4-hydroxyphenyl)-3-hydroxy-1,3heptadien-5-one isolated from A. blepharocalyx showed antiplatelet activity (Doug et al, 1998). Keihanian et al (2018) reported anti-coagulant activities of curcumin and its role in treatment of cardiovascular diseases.…”
Section: Anti-coagulant Activitymentioning
confidence: 99%